The Use of Biologic Modifiers as a Bridge to Hematopoietic Cell Transplantation in Primary Immune Regulatory Disorders - Arnold, Danielle E.; Chellapandian, Deepak; Leiding, Jennifer W. (Frontiers in Immunology, 2021)
Recently, primary immune regulatory disorders have been described as a subset of inborn errors of immunity that are dominated by immune mediated pathology. As the pathophysiology of disease is elucidated, use of biologic modifiers have been increasingly used successfully to treat disease mediated clinical manifestations. Hematopoietic cell transplant (HCT) has also provided definitive therapy in several PIRDs. Although biologic modifiers have been largely successful at treating disease related manifestations, data are lacking regarding long term efficacy, safety, and their use as a bridge to HCT. This review highlights biologic modifiers in the treatment of several PIRDs and there use as a therapeutic bridge to HCT.